2020
DOI: 10.1109/access.2020.3012596
|View full text |Cite
|
Sign up to set email alerts
|

Variable High Precision Wide D-Band Phase Shifter

Abstract: This paper proposes a new concept of designing compact high precision millimeter-wave wideband variable phase shifters. The phase shifter is implemented with a stacked shim with extremely short length of 0.9 mm and two waveguide flange adaptors with length of 0.5mm. High precision phase shifting is achieved over entire D-band (110-170 GHz) by rotating the shim 90 degrees from aligned to perpendicular with consistent impedance matching performance. In addition, a glide-symmetric holey electromagnetic bandgap (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Therefore, the use of periodic structures, such as metallic pins, was proposed in the literature [83]. Similar to metallic pins, glide-symmetric holes can also be used to reduce the leakage [64], [84]. Fig.…”
Section: B Flangesmentioning
confidence: 99%
“…Therefore, the use of periodic structures, such as metallic pins, was proposed in the literature [83]. Similar to metallic pins, glide-symmetric holes can also be used to reduce the leakage [64], [84]. Fig.…”
Section: B Flangesmentioning
confidence: 99%
“…Furthermore, while the stop-band between the first two modes is suppressed in glide-symmetric structures, a large stop-band exists at higher frequency [23][24][25]. This stop-band has been used to design low-cost gap waveguides [26] and filters [27] and to reduce the leakage between waveguide flanges [28,29]. These attractive properties have inspired the development of several semi-analytical methods for the analysis of glide-symmetric structures using circuit models [25,30,31], mode-matching [32][33][34][35], or the multimode transfer-matrix approach [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that glide symmetry broadens the bandwidth of the electromagnetic band gaps (EBGs) in holey periodic structures [6]. This property has been applied to produce cost-effective gap-waveguide components [7], [8], flanges with low-leakage [9], [10], and filters [11]. Glide symmetry also increases the level of anisotropy of periodic structures [12], [13], which can be used, for example, to compress the size of lenses with transformation optics [14], [15].…”
Section: Introductionmentioning
confidence: 99%